Generalized Duality, Hamiltonian Formalism and New Brackets - Duplij, S. (Журнал математической физики, анализа, геометрии, 2014)
It is shown that any singular Lagrangian theory: 1) can be formulated without the use of constraints by introducing a Clairaut-type version of the Hamiltonian formalism; 2) leads to a special kind of nonabelian gauge theory which is similar to the Poisson gauge theory; 3) can be treated as the many-time classical dynamics. A generalization of the Legendre transform to the zero Hessian case is done by using the mixed(envelope/general) solution of the multidimensional Clairaut equation. The equations of motion are written in the Hamilton-like form by introducing new antisymmetric brackets. It is shown that any classical degenerate Lagrangian theory is equivalent to the many-time classical dynamics. Finally, the relation between the presented formalism and the Dirac approach to constrained systems is given. Показано, что любая сингулярная лагранжева теория: 1) может быть сформулирована без привлечения связей с помощью Клеро-версии гамильтонового формализма; 2) приводит к специальному виду неабелевой калибровочной теории, которая подобна пуассоновой калибровочной теории; 3) может быть сформулирована как многовременная классическая динамика. Обобщение преобразования Лежандра на случай нулевого гессиана проведено с использованием смешанного (обертывающего/общего) решения многомерного уравнения Клеро. Уравнения движения записываются в гамильтоновой форме с помощью введения новых антисимметричных скобок. Отмечено, что любая классическая система с вырожденным лагранжианом эквивалентна многовременной классической динамике. В заключение приведено взаимоотношение представленного формализма и теории связей Дирака.